2015
DOI: 10.1371/journal.pone.0116596
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD44 Variant 9-Expressing Cancer Stem Cells Might Attenuate the Efficacy of Chemoradioselection and Worsens the Prognosis of Patients with Advanced Head and Neck Cancer

Abstract: BackgroundAt our institute, a chemoradioselection strategy has been used to select patients for organ preservation on the basis of response to an initial 30–40 Gy concurrent chemoradiotherapy (CCRT). Patients with a favorable response (i.e., chemoradioselected; CRS) have demonstrated better outcomes than those with an unfavorable response (i.e., nonchemoradioselected; N-CRS). Successful targeting of molecules that attenuate the efficacy of chmoradioselection may improve results. Thus, the aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 30 publications
(41 reference statements)
0
34
0
Order By: Relevance
“…In the present study, we examined 63 MIBC patients who under- tissue samples has also been reported in various cancers, such as gastric, 24 hepatocellular, 25 and head and neck cancers. 26 In the field of urothelial cancer, Miyake et al 12 The initial finding of SSZ as a potent inhibitor of xCT was investigated in lymphoma cells 14 and increasing numbers of studies reported the anticancer effects of SSZ in various cancers, such as glioma, 27 prostate cancer, 28 and pancreatic cancer. 16 Furthermore, SSZ was shown to enhance the therapeutic efficacy of chemotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we examined 63 MIBC patients who under- tissue samples has also been reported in various cancers, such as gastric, 24 hepatocellular, 25 and head and neck cancers. 26 In the field of urothelial cancer, Miyake et al 12 The initial finding of SSZ as a potent inhibitor of xCT was investigated in lymphoma cells 14 and increasing numbers of studies reported the anticancer effects of SSZ in various cancers, such as glioma, 27 prostate cancer, 28 and pancreatic cancer. 16 Furthermore, SSZ was shown to enhance the therapeutic efficacy of chemotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…The monoclonal antibody used in our study binds to the epitope 1 of CD44, which is expressed in the standard CD44 isoform as well as in his alternative splicing variants . A recent study demonstrated that both populations have important implications for stem cell‐like potential, resulting in poorer outcome and therapeutic resistance . Mechanistically, CD44 expression promotes glutathione production and regulation of redox status, thereby protecting CSCs from reactive oxygen species …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, enrichment in EMT sustains propagation of cells with stem cell‐like characteristics within a tumor . These two processes overlap and share common signaling pathways, such as Notch, BMI‐1, Hedgehog, and Wnt . Activation of these pathways results in increased expression of several proteins, which can in turn be used as surrogate markers to tag cancer stem‐like cell (CSC) potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings suggest that CD44v9-positive cells have a specific function in protecting against ROS, and contribute to features of cancer stem cells. In addition, expression of CD44v9 in tumor tissues has also been associated with tumor recurrence and prognosis in patients with several types of cancer (4,19,20,31,33). Recently, expression levels of CD44v9 in early gastric cancer have also been shown to correlate positively with the risk of recurrence in patients who underwent endoscopic submucosal dissection (21).…”
Section: Methodsmentioning
confidence: 99%